Utility and safety of flexible fiberoptic bronchoscopy in mechanically ventilated children in pediatric intensive care unit. Issue 5 (2nd March 2022) - Sachdev, Anil; Gupta, Neeraj; Khatri, Anuj; Jha, Ganpat; Menon, Geetha R.
Abstract: Objectives: To study the utility, safety, and effects of flexible fiberoptic bronchoscopy (FFB) on oxygenation status, ventilation parameters, and hemodynamics in mechanically ventilated children. Design: Retrospective study. Patients: Children aged >1 month to 18 years suffering from critical medical and surgical diseases. Results: First bronchoscopy data of 131 patients were analyzed. Indication, FFB findings, the microbiological yield from bronchoalveolar lavage, and medical and surgical interventions based on FFB results were recorded. Hemodynamic and ventilation parameters before, during, and 3 h after FFB were also captured. The majority of bronchoscopies were done for diagnostic purposes with a positivity rate of 90.8%. Retained mucopurulent secretion in the airways was the commonest finding in 60 patients. A cause for weaning or extubation failure could be identified in 83.3%. Post‐FFB radiological resolution of atelectasis was seen in 34/59 (57.6%; p‐value : 0.001) chest radiographs. Forty‐seven medical and 25 surgical interventions were done depending on FFB and BAL findings. There was a significant drop in oxygenation parameters and a rise in heart rate during FFB ( p‐value : <0.0001). The peak inspiratory pressure, positive end‐expiratory pressure, and mean airway pressure increased significantly during bronchoscopy ( p value: <.0001) while patients were on pressure‐regulated volume‐controlled ventilation. All these changes reversed to pre‐FFB levels. There were minor procedure‐related complications. Conclusion: FFB was an important diagnostic and therapeutic tool for mechanically ventilated children and the results helped plan interventions. It was a safe procedure with transient reversible cardiopulmonary alterations.